La Grève au Québec: Une Analyse quantitative exploratoire portant sur la période 1896-1915 - Thwaites, James (Labour / Le Travail, 1984)
Presents and analyzes statistical data on strikes in Quebec during the period 1896-1915. Concludes that there was a significant increase in strikes as compared to the previous half century, that they took place in particular economic sectors, that they were mostly about seeking rather than protecting existing gains or rights, that they were concentrated in the two major urban centres of Quebec City and especially Montreal, that they occurred in the warmer seasons, and that salaries were the principal issue.

In Search of Excellence : Lessons from America's Best-Run Companies - Thwaites, James (Relations Industrielles / Industrial Relations, 1984)
This article reviews the book, "In Search of Excellence : Lessons from America's Best-Run Companies," by T.J. Peters & R.H. Jr. Waterman.

American Working Class History : A Representative Biography - Thwaites, James (Relations Industrielles / Industrial Relations, 1984)
This article reviews the book, "American Working Class History : A Representative Biography," by Maurice F. Neufeld, Daniel J. Leab & Dorothy Swanson.

Essays in Canadian Business History - Thwaites, James (Relations Industrielles / Industrial Relations, 1984)
This article reviews the book, "Essays in Canadian Business History," by Tom Traves.